THE STUDY OF BENTHIC FAUNAIN CANOL CANAL IN RELATION TO ENVIRONEMTAL PARAMETERS, THRISSUR DISTRICT, KERALA - NIMISHA, P.; SHEEBA, S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2015)
The aim of this study is to document the distribution and abundance of benthic animals and physicochemical parameters of water in three selected stations of Canoli canal. The study provides the preliminary details of the benthic fauna. Benthic production is of importance in assessing the biological productivity and demersal fishery of that region. So the baseline data generated from this investigation will be of much use in all future assessment.